MnFe2O4 / SWAC composite nano-microsphere wave-absorbing material and preparation method thereof

By growing MnFe2O4 nanoparticles on modified methylene blue saturated wood activated carbon, MnFe2O4/SWAC composite nanomicrosphere absorbing material was prepared, which solved the problems of narrow bandwidth and large thickness of the existing materials, and achieved significant electromagnetic wave absorption performance in the high-frequency region and green and environmentally friendly characteristics.

CN119898821APending Publication Date: 2025-04-29ANHUI UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510084450.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing electromagnetic wave absorbing materials have the disadvantages of narrow bandwidth and large thickness, and it is difficult to show significant electromagnetic wave absorbing performance in high-frequency regions.

Method used

MnFe2O4 nanoparticles were grown on modified methylene blue saturated wood activated carbon (SWAC) by solvothermal method, and MnFe2O4/SWAC composite nanomicrosphere absorbing material was prepared.

Benefits of technology

It has achieved significantly enhanced electromagnetic wave absorption performance in high-frequency regions, with wide bandwidth, thin thickness, high reflection loss, simple raw material acquisition and low cost, which is in line with the concept of green and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898821A_ABST
    Figure CN119898821A_ABST
Patent Text Reader

Abstract

The invention discloses a MnFe2O4 / SWAC composite nano-microsphere wave-absorbing material and a preparation method thereof. The preparation method comprises the following steps: firstly, preparing SWAC by taking methylene blue saturated wooden activated carbon as a raw material; then dispersing the porous carbon material SWAC in ethylene glycol, and performing ultrasonic treatment to obtain a mixed solution; the preparation method comprises the following steps: dispersing MnCl2 and FeCl3. 6H2O in a mixed solution, adding PEG 4000 and sodium acetate, stirring, transferring the mixture into a high-pressure kettle, heating for a period of time, filtering, washing the obtained precipitate with ionized water and absolute ethyl alcohol, and drying to obtain the MnFe2O4 / SWAC composite nano-microsphere wave-absorbing material. According to the method, the raw materials are easy to obtain, the cost is low, and the prepared composite nano-microsphere wave-absorbing material has the advantages of being wide in bandwidth and thin in thickness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano material preparation, and in particular to a MnFe2O4 / SWAC composite nano microsphere absorbing material and a preparation method thereof. Background Art

[0002] With the rapid development of electronic technology, the problem of electromagnetic wave pollution is becoming increasingly serious, posing a major threat to human health and information security. Therefore, researchers are paying more and more attention to the research on electromagnetic wave absorbing materials. In particular, carbon materials have gained a prominent position due to their low density, excellent chemical stability and high dielectric properties. Biomass carbon, carbon fiber and graphene have all been widely studied in the field of electromagnetic wave absorption. For example, Negi et al. used mango leaf waste biomass as raw material and composite carbonization with epoxy resin to prepare porous carbon, and the best reflection loss at 6.48GHz was -39.57dB. Feng et al. used strawberry petiole-derived carbon fiber as raw material, cobalt-nickel alloy, and prepared porous structure composite materials by solvothermal reaction and calcination. The best reflection loss of the composite material was -40.4dB. Xu et al. synthesized N-doped reduced graphene oxide / hollow cobalt ferrite composite materials with three-dimensional hierarchical porous structure by solvothermal method. The best reflection loss of the composite material was -44.7dB. However, its electromagnetic wave absorption performance generally has the disadvantages of narrow bandwidth and large thickness. Summary of the invention

[0003] The object of the present invention is to provide a MnFe2O4 / SWAC composite nano-microsphere absorbing material and a preparation method thereof. The method has simple raw material acquisition and low cost, and the prepared composite nano-microsphere absorbing material has the advantages of wide bandwidth and thin thickness.

[0004] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing a MnFe2O4 / SWAC composite nano-microsphere absorbing material, comprising the following steps:

[0005] S1, preparation of SWAC using methylene blue saturated wood activated carbon as raw material;

[0006] Weigh the methylene blue saturated wood activated carbon and dry it in an oven, then put it into a tubular oven for calcination, wash the calcined sample with deionized water several times to remove impurities, and finally obtain the porous carbon material SWAC;

[0007] S2, preparing the composite material MnFe2O4 / SWAC by solvothermal method;

[0008] S2-1, dispersing the porous carbon material SWAC obtained in step S1 in ethylene glycol, and ultrasonically obtaining a mixed solution;

[0009] S2-2, MnCl2 and FeCl3·6H2O are dispersed in the mixed solution obtained in step S2-1, and then PEG4000 and sodium acetate are added, and the mixture is transferred to an autoclave after stirring, and filtered after heating for a period of time. The obtained precipitate is washed with ionized water and anhydrous ethanol and then dried to obtain a MnFe2O4 / SWAC composite nano-microsphere absorbing material.

[0010] Preferably, in step S1, the specific parameters of calcination in the tubular oven are: heating to 700° C. at a rate of 5° C. / min under a nitrogen atmosphere and keeping the temperature for 2 h.

[0011] Preferably, in step S2-1, the ratio between the mass of the porous carbon material SWAC and the volume of ethylene glycol is 1 g:100 mL.

[0012] Preferably, in step S2-2, Mn 2+ and Fe 3+ The molar ratio between them is 1:2; the concentrations of MnCl2 and FeCl3·6H2O in the mixed solution are 0.03-0.07 mol / L and 0.06-0.14 mol / L, respectively; the concentrations of PEG 4000 and sodium acetate in the mixed solution are 0.005 mol / L and 0.88 mol / L, respectively.

[0013] Preferably, in step S2-2, heating is performed to 200°C and continued for 10 hours.

[0014] Preferably, in step S2-2, the mixture is stirred in a magnetic stirrer at a rotation speed of 500 rpm for 10-20 min.

[0015] To achieve the above-mentioned purpose of the invention, the present invention also provides a MnFe2O4 / SWAC composite nano-microsphere absorbing material prepared by the above-mentioned preparation method, which exhibits significantly enhanced electromagnetic wave absorption performance in the high-frequency region.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The present invention successfully grows MnFe2O4 nanoparticles on modified methylene blue saturated wood activated carbon (SWAC) by a simple hydrothermal method, and the composite material shows significantly enhanced electromagnetic wave absorption performance in the high frequency region. Compared with pure SWAC, the negative dielectric constant is enhanced, indicating that a metal-like conductive network is formed in the MnFe2O4 / SWAC composite nanomaterial. In addition, the negative dielectric constant can be adjusted by changing the load of MnFe2O4. In the MnFe2O4 / SWAC composite nanomaterial with a thickness of only 1.65mm and a weight of 25wt%, the minimum reflection loss (RL) is -55.57dB. The effective absorption bandwidth can reach up to 4GHz. The raw materials of the present invention are simple to obtain and economical, and it is a secondary utilization of solid waste, which conforms to the concept of green and sustainable development. Under simple composite steps, excellent microwave absorption performance with thin thickness, wide bandwidth and high reflection loss is achieved, which provides guidance for the preparation of nanocomposite materials with good EMW absorption performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 XRD patterns, Raman patterns and hysteresis loops of the samples prepared in Examples 1-3: (a) XRD, (b) Raman; (c) hysteresis loop of SCM-2;

[0019] Figure 2 The SEM images of the samples prepared in Examples 1-3 and the EDS spectrum of the sample SCM-2 prepared in Example 1; (a) is SCM-1 with a scale of 1 μm, (b) is SCM-2 with a scale of 1 μm, (c) is SCM-3 with a scale of 1 μm, (d) is SCM-1 with a scale of 200 nm, (e) is SCM-2 with a scale of 200 nm, (f) is SCM-3 with a scale of 200 nm, and (gj) are EDS spectra of SCM-2;

[0020] Figure 3 XPS graph of sample SCM-2 prepared in Example 1: (a) full spectrum, (b) O 1s, (c) Fe 2p, (d) Mn2p;

[0021] Figure 4 Reflection loss diagrams of the samples prepared in Examples 1-3: (a) SCM-1; (b) SCM-2; (c) SCM-3. DETAILED DESCRIPTION

[0022] The present invention is further described in detail below in conjunction with specific embodiments.

[0023] The methylene blue saturated wood activated carbon used in the following examples was derived from wood activated carbon that had treated methylene blue dye wastewater in the laboratory; deionized water (DI, 18.25 MΩ) without additional purification; FeCl3·6H2O, MnCl2·6H2O, ethylene glycol (EG), polyethylene glycol 4000 (PEG 4000), and CH3COONa (NaAc) were analytical reagents purchased from Sinopharm Chemical Reagent Co., Ltd.

[0024] Example 1

[0025] A method for preparing a MnFe2O4 / SWAC composite nano-microsphere wave absorbing material comprises the following steps:

[0026] S1, preparation of SWAC using methylene blue saturated wood activated carbon as raw material;

[0027] First, 1.5 g of methylene blue saturated wood activated carbon was weighed in a magnetic boat, then taken out and dried in an oven at 100 °C, and then placed in a tubular oven, heated to 700 °C at a rate of 5 °C / min under a nitrogen atmosphere, and kept warm for 2 h; the calcined sample was washed several times with deionized water to remove impurities, and finally a porous carbon material SWAC was obtained;

[0028] S2, preparing the composite material MnFe2O4 / SWAC by solvothermal method;

[0029] S2-1, dispersing 0.5 g of the porous carbon material SWAC obtained in step S1 in 50 ml of ethylene glycol, and ultrasonicating for 30 min to obtain a mixed solution;

[0030] S2-2, 0.31g MnCl2 (2.5mmol) and 1.35g FeCl3·6H2O (5mmol) were dispersed in the mixed solution obtained in step S2-1, and then 1.0g PEG 4000 and 3.6g sodium acetate were added. After vigorous stirring for 15min, the mixture was transferred to a 100ml autoclave, heated to 200°C for 10h and then filtered. The obtained precipitate was washed with deionized water and anhydrous ethanol, and dried at 60°C for 12h to obtain a MnFe2O4 / SWAC composite nanosphere absorbing material (named SCM-2).

[0031] Example 2

[0032] The difference between this embodiment and embodiment 1 is that Mn 2+ and Fe 3+ The added molar amounts of are 1.5 mmol and 3 mmol respectively, and the other steps are the same as those in Example 1. SCM-1 is obtained in this example.

[0033] Example 3

[0034] The difference between this embodiment and embodiment 1 is that Mn 2+ and Fe 3+ The added molar amounts of are 3.5 mmol and 7 mmol respectively, and the other steps are the same as those in Example 1. SCM-3 is obtained in this example.

[0035] Smart Lab SE diffractometer was used to perform X-ray diffraction (XRD) test to analyze the structural phase of the material. The scanning speed was adjusted to 5°C / min, and the scanning range was 10° to 80°. Scanning electron microscope (SEM) was used to analyze the microstructure of the sample. Raman spectra were collected by Raman microscope. Elemental analysis was performed by X-ray electron spectroscopy, and the specific surface area of ​​the sample was determined by specific surface area analyzer. The sample was mixed with paraffin in a ratio of 2.5:7.5 and pressed into a ring shape. The electromagnetic parameters of the sample were evaluated using a vector network analyzer (AV3672B-S).

[0036] The structure of SCM was analyzed by XRD, such as Figure 1 As shown in a, the XRD pattern of the composite material SCM shows that it has characteristic absorption peaks at 2θ = 29.59°, 34.88°, 42.40°, 56.02°, and 61.52°. These peaks are consistent with the diffraction peaks of the (202), (311), (400), (333), and (440) crystal planes of MnFe2O4 crystals (PDF No.38-0430), and the absorption peaks are relatively sharp. Combined with the SEM results, it can be inferred that MnFe2O4 crystals are generated in the coating layer and have a high degree of crystallinity. Raman spectroscopy can explain the degree of graphitization of carbon materials. Figure 1 As shown in b, the sample presents two prominent characteristic peaks, 1326.7cm -3 and 1579.1cm -3 The peak is the characteristic peak of the Raman spectrum of carbon. -3 ) is related to defective graphite structure and disordered carbon, and the G band (1,579.1 cm -3 ) is related to the bond stretching of sp2 hybridized carbon. Usually, the intensity ratio of D band to G band (I D / I G ) is usually used to measure the degree of graphitization of carbon atoms. D The larger it is, the higher the disorder. Figure 1 I of the sample in b D / I G The value of sp2 hybridized carbon in the sample gradually decreases, the disordered carbon gradually increases, the degree of graphitization decreases, and the defects begin to increase with the increase of temperature. The magnetic properties of SCM-2 were characterized by a vibrating sample magnetometer. Figure 1As shown in c, the specific magnetization intensity of the SCM-2 sample is as high as 38.92emu·g -1 , so the magnetic field can be used for efficient magnetic separation. The hysteresis loop of SCM-2 is long and narrow, indicating that its coercive force is small and it has soft magnetic characteristics.

[0037] The microstructure and element distribution of SCM were analyzed by SEM, such as Figure 2 As shown. Figure 2 b and 2c show that a large number of nanoparticles are generated on the surface of SCM, with a particle size between 20 and 100 nm, and the particles accumulate to form a coating layer with rich voids. Figure 2 From the EDS element mapping of g~2j, it can be seen that Fe, Mn, O and other elements are evenly distributed on the surface of the composite material, indicating that the nanoparticles in the coating layer should be iron-manganese compounds. A large number of magnetic nanoparticles can provide eddy current loss and enhance the wave absorption performance of the sample.

[0038] In order to further study the chemical state of each element on the surface of SCM-2 composite material, XPS characterization was carried out. Figure 3 As shown in a, there are C, O, Mn and Fe elements in SCM-2. The XPS spectrum of O1s ( Figure 3 The peak shape of b) is asymmetric. After peak fitting by software, three characteristic peaks at 531.1, 530.1 and 528.7 eV are obtained, corresponding to adsorbed oxygen, hydroxyl oxygen and metal oxide respectively. Figure 3 c), Fe2p splits into Fe2p 1 / 2 and Fe2p 3 / 2 The double peaks are located at 723.6 and 709.4 eV, respectively, and are accompanied by satellite peaks at 717.5 and 712.0 eV, respectively, indicating that the valence state of the Fe element in the sample is +3. From the XPS spectrum of Mn2p ( Figure 3 d) It can be seen that Mn2p splits into Mn2p with binding energies of 651.8 and 640.3 eV respectively. 1 / 2 and Mn2p 3 / 2 The double peaks indicate that the surface manganese element is Mn 2+ XPS results further prove that MnFe2O4 is loaded on the surface of SWAC.

[0039] Reflection loss (RL) is an important indicator for evaluating the EMW absorption performance of MnFe2O4 / SWAC absorber. The RL value can be obtained by the following formula (1) and formula (2):

[0040]

[0041] RL(dB)=20log|(Z in -Z0) / (Z in+Z0)| (2)

[0042] In the formula, Z in , Z0, c, f, d, ε r , μ r They are free space impedance, input impedance, light speed, EMW frequency, MnFe2O4 / SWAC absorber thickness, complex dielectric constant and complex magnetic permeability. In order to evaluate the absorption performance of EMW, Figure 4 The RL values ​​of SCM-1, SCM-2 and SCM-3 are given. In the 2-18 GHz frequency band, the EMW absorption performance of SCM-1 and SCM-3 is always weak. However, SCM-2 has absorption peaks in the C, X and Ku bands, basically covering the mid-frequency band and the high-frequency band, indicating that the MnFe2O4 / SWAC composite material has multi-band absorption performance. At 1.65 mm, the minimum RL of SCM-1 is -16.23 dB at 14.56 GHz, and the maximum effective absorption bandwidth (EAB) is 3.36 GHz at 4.0 mm, as shown in Figure 2. Figure 4 As shown in b. The SCM-2 sample exhibits strong EMW absorption performance in multiple bands. Figure 4 In b, the minimum RL value at 16.08 GHz at 1.65 mm is -55.57 dB. With the increase of thickness, the absorption peak of the material moves from high frequency to low frequency; and the SCM-3 sample has the weakest absorption performance, which is related to the mass of the introduced MnFe2O4. The electromagnetic properties of the composite material are regulated by the mass of MnFe2O4. The EMW absorption performance of the MnFe2O4 / SWAC composite material mainly comes from the following aspects: First, the composite material can play a synergistic role in different components, combining the strong dielectric loss of SWAC with the magnetic loss of MnFe2O4 nanoparticles. Secondly, the introduction of MnFe2O4 can improve the magnetic properties and dielectric properties of SWAC, thereby significantly improving the overall impedance matching level.

[0043] In summary, high-performance microwave absorbing materials can be effectively prepared by heat treating SWAC and growing MnFe2O4 nanoparticles on it as a carbon matrix. The dielectric constant and magnetic permeability of the composite material can be properly adjusted by controlling the amount of MnFe2O4 introduced, so that it has the best impedance matching and the most suitable attenuation constant, thereby changing the microwave absorption performance of MnFe2O4 / SWAC. 2+ :Fe 3+When the ratio of carbon-based absorbers is 2.5mmol:5mmol, the prepared sample SCM-2 has a bandwidth of 4.0GHz and a reflection loss of -55.57dB when the thickness is 1.65mm and the filling rate is 25%. In addition, the sample thickness is changed from 3.45mm to 0.45mm, which can cover the frequency range of 4-18GHz. Compared with the previous research on carbon-based absorbers, the raw materials of the present invention are simple to obtain and economical, and it is a secondary utilization of solid waste. It combines the concept of green and sustainable development and achieves excellent microwave absorption performance with thin thickness, wide bandwidth and high reflection loss in a simple composite step.

Claims

1. A method for preparing a MnFe2O4 / SWAC composite nano-microsphere absorbing material, characterized in that: The following steps are involved: S1, preparation of SWAC using methylene blue saturated wood activated carbon as raw material; Weigh the methylene blue saturated wood activated carbon and dry it in an oven, then put it into a tubular oven for calcination, wash the calcined sample with deionized water several times to remove impurities, and finally obtain the porous carbon material SWAC; S2, preparing the composite material MnFe2O4 / SWAC by solvothermal method; S2-1, dispersing the porous carbon material SWAC obtained in step S1 in ethylene glycol, and ultrasonically obtaining a mixed solution; S2-2, MnCl2 and FeCl3·6H2O are dispersed in the mixed solution obtained in step S2-1, and then PEG 4000 and sodium acetate are added. After stirring, the mixture is transferred to an autoclave, heated for a period of time and then filtered. The obtained precipitate is washed with ionized water and anhydrous ethanol and then dried to obtain a MnFe2O4 / SWAC composite nano-microsphere absorber material.

2. The method for preparing a MnFe2O4 / C composite nano-microsphere absorbing material according to claim 1, characterized in that: In step S1, the specific parameters of calcination in the tubular oven are: heating to 700°C at a rate of 5°C / min under a nitrogen atmosphere and keeping the temperature for 2h.

3. The method for preparing a MnFe2O4 / SWAC composite nano-microsphere absorbing material according to claim 2, characterized in that: In step S2-1, the ratio between the mass of the porous carbon material SWAC and the volume of ethylene glycol is 1 g:100 mL.

4. The method for preparing a MnFe2O4 / SWAC composite nano-microsphere absorbing material according to claim 1 or 2, characterized in that: In step S2-2, Mn 2+ and Fe 3+ The molar ratio between them is 1:2; the concentrations of MnCl2 and FeCl3·6H2O in the mixed solution are 0.03-0.07 mol / L and 0.06-0.14 mol / L, respectively; the concentrations of PEG 4000 and sodium acetate in the mixed solution are 0.005 mol / L and 0.88 mol / L, respectively.

5. The method for preparing a MnFe2O4 / SWAC composite nano-microsphere absorbing material according to claim 1 or 2, characterized in that: In step S2-2, heating is performed to 200°C for 10 hours.

6. The method for preparing a MnFe2O4 / SWAC composite nano-microsphere absorbing material according to claim 1 or 2, characterized in that: In step S2-2, stir in a magnetic stirrer at a rotation speed of 500 rpm for 10-20 min.

7. The MnFe2O4 / SWAC composite nano-microsphere absorbing material prepared by the preparation method according to any one of claims 1 to 6, wherein the material exhibits significantly enhanced electromagnetic wave absorption performance in the high frequency region.

Citation Information

Cited By

  • Self-repairing wave-absorbing composite material as well as preparation method and application thereof

    CN120590785A